Songkok Nasional and the Construction of National Symbolism: A Hadith Perspective through Charles Sanders Pierce’s Semiotics - Ilham Syamsul; Nuryanto Nuryanto; Fakhri Ilham Syarifudin; Anggi Radar Bintara; Muhammad Alfreda Daib Insan Labib (Jurnal Ushuluddin, 2026)
Songkok nasional is a typical Indonesian attribute that contains various cultural, religious, and even state symbols. Meanwhile, there is a hadith that talks about the symbol of human identity, namely the hadith ‘imāmah. Therefore, this article wants to explore the relationship between symbolic meanings built in the songkok nasional and the hadith of ‘imāmah using Charles Sanders Peirce's semiotic theory. The research method is a qualitative method based on library research. The analysis technique used is descriptive analytical, namely analyzing the data that has been collected and then describing the research results comprehensively. The results of this study are through three semiotic relations, Songkok Nasional understood as a representation of national identity, which has normative legitimacy through its correlation with the hadith ‘imāmah as the basis for dressing in Islam. This relationship shows that the symbols of clothing, especially head coverings, are not singular, but have layered, contextual, and flexible meanings.